ANALISIS BEBAN KERJA FISIOLOGI DAN PSIKOLOGI KARYAWAN PEMBUATAN BAJU DI PT JABA GARMINDO MAJALENGKA - Lalan Ruslani; Nurfajriah Nurfajriah (Bina Teknika, 2015)
This study was conducted to determine the physiological workload and psychological employee mental burden of making clothes at each work station. The study was conducted at six work stations that work station QC Jodoh, Linking, QC Lampu, Pantek, Sontek and Obras. Calculation of physiological workload carried using the NASA-TLX. Physiological workload calculation results showed that the highest energy consumption experienced by the operator at the work station sontek (85,8 Kcal /hour), while the lowest value contained in the work station QC Jodoh (54 Kcal/hour). This job classified into light workload due to smaller than 100-200 Kcal/hour (according to Decree No. 5 1of 1999). Measurement of psychological workload on each carrier based questionnaire NASA-TLX which has been filled by 18 operators, obtained a total rating of each indicator psychological workloads different. This shows that the difference in the psychological workload experienced by the operator on each indicator.